Integration of Generative Artificial Intelligence (GAI) in Academic and Engineering Sectors to Enhance Employee Productivity - AlNaqbi, Humaid Abdalla (2024)
A Master of Science thesis in Engineering Systems Management by Humaid Abdalla Al Naqbi entitled, “Integration of Generative Artificial Intelligence (GAI) in Academic and Engineering Sectors to Enhance Employee Productivity”, submitted in August 2024. Thesis advisor is Dr. Zied Bahroun and thesis co-advisor is Dr. Vian Ahmed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).